The unfinished manner - Harries, Elizabeth Wanning (Univ. Press of Virginia, 1994)
The Unfinished Manner examines the fragments produced by European writers and artists in the eighteenth century and earlier, fragments that were not the result of an inability to finish either texts or buildings but rather deliberate refusals to make the traditional gestures of conclusion. Most books published in the past few years on the fragment and the unfinished see it as a peculiarly
Keywords: Aufsatzsammlung; Fragmenten; Letterkunde; Literatur; Closure (Rhetoric); Literature; Modern; Fragment; Ruinenbau